A radiological approach to benign and malignant lesions of the mandible. Issue 4 (April 2015) - Harmon, M.; Arrigan, M.; Toner, M.; O'Keeffe, S.A.
<x xml:space="preserve">Abstract</x> There is a wide range of pathological conditions that affect the mandible. Although some lesions demonstrate characteristic imaging features, many of the pathological processes encountered in the mandible often exhibit similar imaging appearances resulting in uncertainty for the reporting radiologist. Many mandibular lesions remain impossible to distinguish without histological analysis. Therefore, this review aims to reassure the radiologist that although imaging findings may not always lead to a specific diagnosis, they narrow the differential diagnosis and guide further work-up. In this regard, we aim to provide a clinically useful framework and approach for radiologists to use when they encounter lesions within the mandible.